Terahertz photoneuromodulation of lateral orbitofrontal cortex neurons ameliorates stress-induced depression and cognitive impairment - Yuanyuan He; Jing Ma; Yun Yu; Junkai Yin; Ge Gao; Yifang Yuan; Hao Ruan; Xueqing Yan; Zihua Song; Chao Chang (Fundamental Research)
Depression imposes a staggering global socioeconomic burden. Current pharmacotherapies face major limitations, including slow efficacy, adverse effects, and non-response rates of up to 55%, necessitating novel therapeutic modalities. This study introduces terahertz (THz) photoneuromodulation as an innovative physical intervention for depression, offering several advantages over conventional pharmacological or optogenetic approaches. Mild THz photoneuromodulation circumvents the need for exogenous agents or genetic modifications, mitigating potential risks while precisely modulating neurotransmitter levels and neuronal excitability to alleviate depression-like behaviors. In a chronic restraint stress (CRS) mouse model, THz photostimulation rapidly attenuated hyperactivity and increased serotonin levels by 107.5% ± 45.3% in lateral orbitofrontal cortex glutamatergic neurons (OFCGlu) compared to those treated with antidepressants. This led to marked improvements in depressive-like behaviors and cognitive function. Furthermore, THz modulation of OFC activity recapitulated the effects of chemogenetic inhibition, underscoring the OFC's pivotal role in regulating depressive states. This research unveils THz photoneuromodulation as a promising, safe, rapid-acting, and durable neurotherapeutic strategy addressing persistent unmet needs in depression treatment.